2021
DOI: 10.3390/f12050641
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Applicability of Wood and Crop Residues for the Production of Wood Composites

Abstract: Due to high levels of volatility in both the agricultural and the forestry commodity markets, specifically, of timber and agricultural crops, it is important to identify the risks associated with the stability of supplies necessary for the production of composite materials in the Czech Republic. This study aims to accurately estimate the availability of selected raw materials that contain lignocellulose over the next 20 years. In addition, their suitability for the production of composite materials is assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(80 reference statements)
0
3
0
1
Order By: Relevance
“…La biomasa es la materia orgánica producto de los vegetales, animales, microorganismos [49], residuos agroindustriales y urbanos, representando el 10%-14% como industria suministradora anual de energía en el mundo equivalente a 1.25 millones de toneladas de petróleo [50] y las grandes industrias lo emplean para producir bioasfalto [51].…”
Section: Modificación Del Asfalto Con Biomasaunclassified
“…La biomasa es la materia orgánica producto de los vegetales, animales, microorganismos [49], residuos agroindustriales y urbanos, representando el 10%-14% como industria suministradora anual de energía en el mundo equivalente a 1.25 millones de toneladas de petróleo [50] y las grandes industrias lo emplean para producir bioasfalto [51].…”
Section: Modificación Del Asfalto Con Biomasaunclassified
“…[12][13][14][15] The introduction of natural fibers into the polymer matrix improves the moisture resistance and degradation ratio of the resultant materials due to the availability of wood hydroxyl groups favor water absorption and accumulation in its cavities. [16][17][18][19][20] Eventually, it increases the possibility of environmental degradation of plastics and turns the final composite into a biodegradable bio-composite. 9,21,22 However, the major drawbacks of worldwide application of WPC, the brittleness and higher weight compared with natural wood, still remain one of the main researchers' interests.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, WPC are used in various applications such as floor coverings, body and roof of buildings, door and window frames, automotive industries, home appliances, and so forth 12–15 . The introduction of natural fibers into the polymer matrix improves the moisture resistance and degradation ratio of the resultant materials due to the availability of wood hydroxyl groups favor water absorption and accumulation in its cavities 16–20 . Eventually, it increases the possibility of environmental degradation of plastics and turns the final composite into a biodegradable bio‐composite 9,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of wood and crop residues for wheat straw and canola straw, according to availability in the Czech Republic, lignocellulosic raw material, moisture, and fibre properties, was realized by Procházka et al [6], and the most suitable candidate for wood-based composites was identified as soft wood. Regarding the evaluation of the fruit trees as solid biomass for briquettes production, there are studies on guava wood that present negative results, as the measured Sulphur content (0.063%) and ash content (3.74%) exceeded the allowed limits for graded wood briquettes [7].…”
Section: Introductionmentioning
confidence: 99%